(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In order to deliver active pharmaceutical ingredients (APIs) for dermatological, pharmacological, and aesthetic uses, the skin barrier must be breached. Chemical permeation enhancers, or CPEs, are chemicals that interact with the components of the stratum corneum (SC), the outermost and rate-limiting layer of the skin, increasing the permeability of the SC. The pace at which new CPEs are discovered is hampered by the resource-intensive nature of designing and testing new CPEs. Designing CPEs could be sped up by in-silico screening in a strict skin model. In this work, we ran multilayer skin lipid matrix coarse-grained (CG) molecular dynamics (MD) simulations with CPEs present. Alcohols, esters, and fatty acids are among the several chemical functions from which the CPEs are selected. An in-silico skin model with several layers was created. Additionally, the CG parameters for permeation enhancers were created. In silico research was done on the interactions between CPEs and SC lipids at three different CPE concentrations: 1% w/v, 3% w/v, and 5% w/v. It was shown that the partitioning and difusion coefficients of CPEs in the SC lipids were strongly dependent on size and structure. These dependencies are explained by structural characteristics as the order parameter, area per lipid, and radial distribution function. Finally, the modeling findings are compared with experimentally documented effects of CPEs on skin from the literature. The simulation-derived trends show excellent agreement with the experimental results. The research shown here supports the use of in-silico models in the creation, evaluation, and testing of new and useful CPEs.